Third Party Service Provider Selection Using TOPSIS based Approach (A Case Study of Ghana Manganese Company) - Amoah Daniel Ayisi; Ming Yin (International Journal of Engineering and Management Research, 2023)
The business strategy structure of a logistics firm is determined by its well-integrated supply chain. A lot of companies fail to structure their business strategy models as their line of activities permit them to improvise. Third party service providing has been a strategic planning implementation and enforcement of many organizations to achieve their objective as an organization. In the last few decades, third party service providers have upgraded their ability or capacity to support organizations engaging them in their activities which is or could be performed in-house. The ultimate aim of this research was to ascertain a service provider for the road haulage activities of GMC, the Ghana Manganese Company as a case study and also to aid in the restructuring of the company’s business strategy model using the Technique for Order of Preference by Similarity to Ideal Solution TOPSIS approach. In addition, the shipping and logistics manager of the case company emphasized that the four selection criteria comprising “Cost of delivery”, “compatibility”, “reputation”, and “certification” should be given due consideration as a priority among the other criterion for selection and scrutiny process. As a result, it will be efficient and responsive for the researcher to simulate a best service provider for the road haulage activities of Ghana Manganese Company.